Designing an Optimized Constructed Wetland System with Circular Sustainability for Wastewater Treatment in Macao - Lei, Micaela (University of Saint Joseph, 2020)
Keywords: Master of Environmental Sciences and Management (MESM); University of Saint Joseph

The Status of Mangroves in Macao and the Efficacy of Localized Environmental Educational Intervention on School Students' Environmental Knowledge - Loi Hoi Kei (University of Saint Joseph, 2020)
Keywords: Master of Environmental Sciences and Management (MESM); University of Saint Joseph

Green Space in Macau: Comparative Analyses and Suggestions for New Reclamation Areas - Xiao, Yuan Bin (University of Saint Joseph, 2020)
Keywords: Master of Environmental Sciences and Management (MESM); University of Saint Joseph

Single-Use Plastic Assessment in Macau Hospitality Industry: Bottled Water as a Case Study - Ao Ieong, Kin San (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Environmental Sciences and Management (MESM); University of Saint Joseph

The Effect of Temporal Variation in Noise Exposure on Hearing and Inner Ear in the Zebrafish Model - Kuan, Chi Kin (University of Saint Joseph, 2021)
Keywords: Master of Environmental Sciences and Management (MESM); University of Saint Joseph

Mangroves as a Nature-Based Solution for Coastal Water Eutrophication in Macao Sar China - Lai, Wai Ian (University of Saint Joseph, 2021)
Keywords: Master of Environmental Sciences and Management (MESM); University of Saint Joseph

Green Roof Application in Macao SAR - Noblesala, Marco Paulo R. (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Environmental Sciences and Management (MESM); University of Saint Joseph

Impact of Vessel Traffic on Underwater Soundscape and Marine Mammals in the Pearl River Delta - Wong, Man Ieng (University of Saint Joseph, 2021)
Keywords: Master of Environmental Sciences and Management (MESM); University of Saint Joseph

LIFE CYCLE ASSESSMENT OF CONSTRUCTED WETLAND SYSTEMS FOR TOURISM UNITS WASTEWATER TREATMENT - Lo, Weng In (University of Saint Joseph, 2022)
With water being an essential for life on Earth, it is vital to preserve it and regenerate it, in order to be available for a myriad of uses. Though many types of wastewater management and treatment are available, most rely on high energy input and are therefore not ideal for many circumstances. Constructed wetlands (CW) are an alternative nature-based solution to be applied to wastewater treatment. This study undertakes a Life-Cycle Assessment (LCA) of a CW as a means of wastewater treatment and aims to understand how these systems can be an environmentally conscious alternative. The CW under study is located in a rural mountain area in the north of Portugal. Receives wastewater from a tourism unit and operates with horizontal subsurface. The LCA analyses the CW through the construction, operation (treatment), and composting phases. This approach allows the entire scope of the life cycle to be included, of which, the composting phase has been absent in similar LCA previously undertaken. Analysis focuses on the impact categories: Ozone Layer Depletion Potential, Global Warming Potential, Acidification Potential, Eutrophication Potential and Human Toxicity Potential. Of the five categories, none increase during the treatment phase, and indeed, Acidification Potential, Eutrophication Potential, and Human Toxicity potential all decrease. Ozone Layer Depletion Potential and Global Warming Potential increase significantly during the construction and composting phases respectively. Both can be rationalized, with the former being a result of heavy diesel machinery use in construction and the latter a natural byproduct of composting. The results are net positive and display the ability for CW as a low energy wastewater treatment which can limit environmental impact by choice of construction and composting methodology
Keywords: Lifecycle assessment; Master of Environmental Sciences and Management (MESM); University of Saint Joseph; constructed wetland; wastewater treatment

INDOOR AIR QUALITY (IAQ) MANAGEMENT IN MACAO: MONITORING PARTICULATE MATTER (PM10 AND PM2.5) AT THE RENOVATION SITE IN LARGE SHOPPING MALLS - Chan, Weng Ian (University of Saint Joseph, 2023)
"Over time, the large shopping malls in Macao will require some changes to improve space utilization, resulting in renovation projects that affect indoor particulate matter (PM10 and PM2.5) concentrations. Employees work long hours in an environment where the ambient air quality is poor, directly affecting their work efficiency. Nonetheless, the concentration of PM produced by the interior renovation of shopping malls has yet to receive particular attention. Therefore, this study will investigate IAQ, in particular, PM10 and PM2.5 in large-scale shopping mall renovation projects in three different indoor locations (i.e., public, renovation, and construction areas) to understand the causes of indoor PM10 and PM2.5. This study will collect on-site PM data for analysis, examine whether the current control measures are appropriate and propose some improvements. The data collected will be compared with IAQ standards from the World Health Organization (WHO) and the Macao Meteorological and Geophysical Bureau (SMG), specifically PM concentrations. The research results can provide a reference guide for decision-makers, management, construction teams, design consultant teams and renovation teams of large-scale projects. In addition, the monitoring of IAQ can ensure a comfortable environment for employees and customers."
Keywords: Construction Dust; Health Exposure; PM Monitoring; Particulate Matter; Thesis and Dissertations Master of Environmental Sciences and Management (MESM); University of Saint Joseph

CHARACTERIZARION OF ENVIRONMENTAL NOISE IN MACAO S.A.R. OVER THE PAST DECADE: IMPLICATIONS FOR NOISE POLLUTION MANAGEMENT - Deng, Ziyang (University of Saint Joseph, 2023)
With the rapid urban development, Macao SAR has become one of regions with the with highest population density in the world, characterized by high traffic flow and dense building aggregations. Noise has become one of the major environmental problems in Macao. Besides having an impact on human health and wellbeing, noise pollution is known to impact ecological systems and the image of a place. Before proposing a plan to reduce noise pollution, it is necessary to have a general understanding of the current noise levels in Macao, how they have changed over time and the main noise pollution sources and environmental concerns. This dissertation relies on the publicly available data from DSPA (Macao Environmental Protection Bureau) monitoring stations concerning noise levels over the past decade. The main research goals were: 1) Characterize changes in noise levels from 2010 to 2021 during daytime, nighttime, and full-day from multiple noise stations located in Macao, Taipa, and Coloane Peninsula; and 2) associate changes in noise levels with potential factors such as location, number of residents/tourists, number of vehicles, among others. This work provides an important framework for future studies concerning noise monitoring and mitigation strategies
Keywords: Environmental policies; Legislation; Master of Environmental Sciences and Management (MESM); Noise management; Noise pollution; University of Saint Joseph; mitigation

Food Waste Management In Macau: Assessing Public Awareness, Recycling Facilities, And Policy Implementations In Comparative Perspective - Hoi, Hang Ian (University of Saint Joseph, 2023)
Food waste has become an increasingly pressing issue worldwide, and Macau is no exception. A substantial portion of municipal solid waste in Macau is comprised of organic waste, with household food waste being a significant contributor. This can be attributed to households purchasing excessive food, preparing more than necessary, or not consuming items before they spoil, leading to detrimental resource and environmental impacts, particularly in the form of greenhouse gas emissions. It is crucial for Macau to develop a sustainable food waste management system that fosters prevention and responsible consumption and to develop food waste recycling habits among its residents. This study employed a two-pronged approach: a literature review of food waste source separation policies and practices in four neighboring regions to identify adaptable good practice examples for Macau, and a questionnaire survey completed by 143 local residents. The survey aimed to comprehend residents' behaviors and awareness regarding food waste prevention and treatment, evaluate their satisfaction with Macau's existing food waste recycling program, examine their resistance and motivation toward participating in the recycling program, and assess their attitudes toward implementing a polluter-pays-principle system in Macau. The survey aimed to provide insights into the current state of household food waste in Macau and inform future waste management policies and strategies of stakeholders. The survey findings highlight the need for enhanced public awareness and education on food waste prevention. Additionally, upgrading recycling facilities may encourage residents to participate more actively in food waste recycling. Ultimately, implementing suitable policies can help prevent food loss and waste and regulate food waste generation and elevate recycling rates. This study offers preliminary recommendations for policymakers or government entities as a orientation for future planning
Keywords: Food Loss and Waste (FLW); Food Waste Hierarchy; Food Waste Management; Food Waste Separation; Sustainable Development Goals (SDGs); Thesis and Dissertations Master of Environmental Sciences and Management (MESM); University of Saint Joseph

NATURAL HAZARDS AND THE ROLE OF MANGROVES AS A NATURE-BASED SOLUTION FOR COASTAL PROTECTION IN MACAO SAR - Lam, Sut Ieng (University of Saint Joseph, 2023)
The inundation problem in Macao is getting more attention recently, especially after the destructive impacts of typhoons Hato (2017) and Mangkut (2019). The inundation caused by storm surges is getting more severe with the rapid sea-level rise in Macao. Moreover, the potential threat of a tsunami in Macao, may be enhanced with rising sea-level. This research evaluated the risk of coastal hazards in Macao by analyzing the local meteorological data. The results of the analysis indicate a rising trend in the tropical cyclone intensity and more severe storm surges are expected to occur in the future. Moreover, this research explores the potential of Nature-based Solutions (NbS), particularly mangroves, to address the inundation problem in Macao. The study included a preliminary laboratory-based experiment and the application of local mangroves data in numerical models. The results of the experiment and numerical models demonstrate the ability of mangroves to attenuate waves. These findings, although preliminary, indicate that mangroves could be a promising NbS to address inundation issues in Macao. To effectively implement this NbS, further field investigations are needed to measure attenuation in-situ, as well as determine optimal locations for mangrove restoration projects
Keywords: Inundation; Mangroves; Master of Environmental Sciences and Management (MESM); Nature-based solutions; Sealevel rise; Storm surges; University of Saint Joseph; Wave attenuation

EVALUATION OF MANGROVE BLUE CARBON AS A POTENTIAL FOR CLIMATE CHANGE MITIGATION IN MACAU - Lao, Hio Wai (University of Saint Joseph, 2023)
Climate change is a global issue but its impact can be felt locally. Macau SAR has been rapidly developing since the single shift towards a gaming industry-dominated economy, the overwhelming anthropogenic activities contributing to increasing pollution. Mangroves, which play an essential role as the blue carbon system with a high carbon sequestration rate could be a natural base solution to the pollution. This study aims to determine 1) the total organic Carbon (TOC) in the soil of Macau mangrove sites, 2) comparison with the methodology evaluating the organic Carbon, and 3) organic Carbon comparison between Macau and other regions. Soil sampling were processed under the Blue Carbon Initiative guideline, and the samples were divided into two parts for determining the TOC%, combustion method from Hong Kong, and methodology of ashing in our laboratory. The overall estimated TOC% of Macau mangrove sites was 1.29%. There are still a lot of potentials in Carbon storage and for climate change mitigation in Macau
Keywords: Carbon sequestration; Mangroves; Master of Environmental Sciences and Management (MESM); University of Saint Joseph; blue Carbon

MONITORING THE CONCENTRATION OF PARTICULATE MATTER (PM10 AND PM2.5) IN SEVERAL ROADSIDE LOCATIONS IN MACAO - Ma, Fa Chong (University of Saint Joseph, 2023)
Road transportation is one of the main sources of air pollution in Macao. This study mainly explores four major roadside locations with high traffic flow in Macao from March to May 2022 and measures their pollutant concentrations (PM10 and PM2.5), traffic flow and their fuel type, as well as considering the meteorological parameters and pollutant concentration of SMG Macao to analyze the relationship between traffic flow and pollutants on roadside locations. Under the measuring distance between 3 and 6 meters, showing that the four locations had a good correlation with the roadside station data provided by SMG on both weekdays and weekends/holidays (PM2.5: R2 is 0.59 to 0.81 on weekdays and 0.79 to 0.88 on weekends/holidays, p<0.01; PM10: R2 is 0.33 to 0.82 on weekdays and 0.30 to 0.58 on weekends/holidays, p<0.05), the overall PM2.5 is 41 to 86% higher than that of the same period of Macao roadside station (SMG), and 68 to 186% higher than that of Taipa Ambient (SMG), indicating that it is more harmful to daily pedestrians. The overall relationship between PM concentration and traffic flow is small on the long-term scale (PM2.5: R2 is 0.01 to 0.13; PM10: R2 is 0.00 to 0.02). This study also analyzed air quality on EBL, the overall PM2.5 and PM10 decreased by 12.3% to 24.8% compared with non-EBL during the period, so that is indeed beneficial to the reduction of pollutant concentrations. In addition, narrower roads were overall higher when road widths added for comparison. Lastly, meteorological data added for comparison, except for relative humidity, it can be found that there is a significant correlation with long-term pollutants (p<0.05). While previous studies have found that single-day traffic flow is related to the increase in PM concentration, this paper is more inclined to their two-way effect when exploring their long-term relationship
Keywords: Thesis and Dissertations Master of Environmental Sciences and Management (MESM); University of Saint Joseph; air pollution; monitoring campaign; particulate matter; traffic characterization

Macau Ambient Air Pollutants Forecasting By Pollutant Time Series And Meteorological Data Using Machine Learning Methods - Ng, Chung Wang (University of Saint Joseph, 2023)
" Air pollution in Macau has become a serious problem following the Pearl River Delta’s (PRD) rapid industrialization that began in the 1990s. While there has been continual improvement in recent years, harmful air pollutant concentration levels are still common, impacting Macau residents' health and creating long-term medical costs to local society. With this in mind, Macau needs an air quality forecast system that accurately predicts pollutant concentration and an early alert system instead of only daily real-time reminders. Some scholars have previously carried out studies to develop an air quality forecast for Macau by successfully using statistical models. Therefore, pursuant to the outcomes of previous studies, this dissertation aims to build upon research results and explore further possibilities of building a better ML air quality forecast model based on the time series of air pollutants concentration and meteorological data. Four different state-of-the-art ML algorithms were used to create predictive models to forecast PM2.5, PM10, and carbon monoxide (CO) concentrations for the next 24 and 48-hour. These were Support Vector Machine (SVM), Artificial Neural Networks (ANN), Random Forest (RF), and Extreme Gradient Boosting (XGBoost). In addition, Multiple Linear Regression MLR, a standard ML model, was used for this dissertation as a baseline reference for performance comparison. The daily measurements of air quality data in Macau from 2016 to 2021 were collected for this dissertation. The 2020 and 2021 datasets were used for model testing while the four-year data prior to 2020 and 2021 were used to build and train the ML models. The results showed that SVM, ANN, RF, and XGBoost were able to provide a very good performance in building up a 24-hour forecast with higher R2 and lower RMSE, MAE, and BIAS. Meanwhile, all ML models in 48-hour forecasting performance were satisfactory enough to be accepted as a two-day continuous forecast even if the R2 value was lower than the 24-hour forecast. The 48-hour forecasting model could be further improved by proper feature selection based on the 24-hour dataset, using the SHAP value test, and the adjusted R2 value of the 48-hour forecasting model."
Keywords: Air pollution; Macau; Machine Learning; Meteorological features; Thesis and Dissertations Master of Environmental Sciences and Management (MESM); Transboundary pollutants; University of Saint Joseph

INFORMAL RECYCLING IN MACAU: CHALLENGES AND OPPORTUNITIES FOR SUSTAINABLE DEVELOPMENT - Ng, Sut Wa (University of Saint Joseph, 2023)
Informal recycling plays a crucial role in municiapl solid waste management in many cities, particularly in the global South. This study examines the practices, challenges, and opportunities of informal recycling in Macau, a small city and Self Autonomous Region (S.A.R.) in China. Using qualitative research methods, including semi-structured interviews, this study explores the motivations and strategies of informal recyclers, the challenges they face, and the potential for collaboration with formal waste management systems. The findings of this study reveal that informal recycling in Macau is a complex and multifaceted reality and practice that involves a range of actors, from waste pickers to small-scale processors to exporters, all with their specific challenges. Informal recyclers are motivated by economic necessity, and they employ a variety of strategies to collect and process recyclable materials. However, they also face significant challenges, including high rental and transportation costs, lack of manpower, China’s waste import policies and ensuing restrictions, fluctuating global price rates of materials and the unstable income as serious consequence, accompanied by limited support from the local Government. This study also identifies opportunities for sustainable development of informal recycling in Macau, supported by the analysis of data collected via questionnaire survey regarding Macau citizens’ waste separation habits and their willingness to pay for resource separation and recovering process. The identified oppurtunities include establishing partnerships between informal and formal waste management actors, improving the infrastructure, and introducing environmental levy system and consistent policies and regulations. Overall, this study contributes to a better understanding of the role of informal recycling sector in waste management in Macau and provides insights into potential strategies for improving the sustainability of resource and waste management practices in the city
Keywords: Circular Economy (CE); Informal Recycling; Integrated Solid Waste Management (ISWM); Recycline Rate; Sustainable Development Goals (SDGs); Thesis and Dissertations Master of Environmental Sciences and Management (MESM); University of Saint Joseph; Waste Hierarchy